Hubungan Kerapatan Lamun dan Kelimpahan Teripang (Holothuroidea) di Pulau Meosmangguandi Taman Wisata Perairan Padaido-Biak - Tasya M.R. Sihabudin; Vera Sabariah; Abdul Hamid A. Toha; Yuli E. Demana (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Seagrasses and sea cucumbers have a close relationship in determining ecological functions. The purpose of this study was to investigate the relationship between seagrass density and sea cucumber abundance on Meosmangguandi Island, Biak. The research was conducted in August-September 2021 at two stations. The location was chosen purposively on the East side (Station I, conservation location) and the West side (Station II, around residential areas and fishing activities). The 5m line transect method (2.5m to the right and 2.5m to the left) is used to reach the destination. The study found 6 species of seagrass namely C. rotundata, T. hemprichii, E. acoroides, H. pinifolia, H. ovalis and Syringodium isoetifolium, and 9 species of sea cucumbers namely Actinopyga lecanora, A. miliaris, A. mauritiana, Bohadschia similis, Holothuria atra, H. coluber, H. scabra, H. albiventer, and teripang malam. Percentage of seagrass cover at Station I was 85.51% and Station II was 57.71%, with a relative density of seagrass C. rotundata 39.10% and T. hemprichii 27.09%. The relationship between the density of seagrass C. rotundata and the abundance of sea cucumbers A. lecanora 4.285 > X2 (1:0.05); T. hemprichii with A. mauritiana 6.887> X2 (1;0.05); seagrass C. rotundata with A. miliaris 4.285 > X2 (1:0.05); A. miliaris with seagrass H. pinifolia 7.048 > X2 (1:0.05); density of seagrass T. hemprichii with abundance of sea cucumber B. similis: 5.274 > X2 (1:0.05); H. atra 5 > X2 (1:0.05); and H. coluber 5.172 > X2 (1:0.05), indicating an association between seagrass density and sea cucumber abundance.